Perlindungan Hak Cipta Terhadap Karya Seni(Studi Perlindungan Hukum Terhadap Lukisan) - Kusuma, Rio Candra; , Prof. Dr. Absori, S.H., M. Hum (2016)
This research is descriptive with emperial juridical approach. The place used for research is at the Regional Office of the Ministry of Law and Human Right in Yogyakarta and at the residence of painters and artists who had something to do with the object, include: Painters Didit, Painters Arfial Arsad Hakim, and Painters in the park Balekambang Surakarta. This study aims to determine the legal protection for the paintings and works of art to formulate a model of protection against the next painting. Based on this research can be concluded overview of legal protection against painting artwork for the moment it is still lacking, it can be seen from the number of cases that occur but still the leats touched by the law is both compensation as well as from criminal prosecution. The role of law enforcement that it is still lacking in handle violations of copyright. Such violations shows that the lack of awareness that is that is owned by the public about the meaning of appreciate a work is less fit or less according to the artists them sleves